Guatemala : 2016 Article IV Consultation-Press Release; Staff Report; Informational Annex. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights that the macroeconomic performance of Guatemala has been solid. The economy grew at 4.1 percent in 2015, slightly above potential, despite a slowdown in public consumption and investment during the crisis. Private consumption was lifted by lower oil prices and strong remittances. The latter also boosted the external position, creating a comfortable reserve cushion. With inflation well anchored, monetary policy was eased to support growth. The macroeconomic outlook remains benign. Growth is set to return to its trend rate of 3.8 percent in 2016 and gradually rise to 4 percent in the medium term, reflecting the positive impact of efforts to increase transparency and efficiency in public spending.